Membangun Metakognisi Siswa dalam Memecahkan Masalah Matematika - Sholihah, Ummu (Institut Agama Islam Negeri (IAIN) Tulungagung, 2016)
Problem solving is a high level of mental activity, where every student has the ability or cognitive styles vary, so the ability to solve problems will also be different. Cognitive styles one can explain the success of individual differences in learning. In evaluating the achievement of learning outcomes currently only gives emphasis on the cognitive goals without regard to the dimensions of cognitive processes, particularly metacognitive knowledge and metacognitive skills. As a result, efforts to introduce metacognition in solving mathematical problems to students is very less. Metacognition is the students âknowledge of cognition involving awareness of their own thinking in terms of the ability of planning, monitoring and evaluation process of thinking. The purpose of this article to describe a strategy to build studentsâ metacognition when solving math problems. With the development of metacognition awareness, students are expected to get used to monitor, control and evaluate what has been and will be done, so that students know and realize the strengths and the weaknesses in solving mathematical problems.